Notes: Effects of Artificial Defoliation on the Growth of Cork Oak - Magnoler, Aldo; Cambini, Anna (Forest Science, 1970)
In Sardinia a single artificial removal of 50 percent or 100 percent of the foliage from Quercus suber L. trees in June caused serious growth losses. The weight of new leaves diminished significantly. Shoot growth and cambial growth were seriously reduced both in the year of treatment and in the following year. Ring width of the cork was greatly reduced in the year of treatment, but recovery was almost complete the following year. The decrease in xylem ring width reduced the generating area of the cork. The reduction in ring width of the cork and generating area resulted in a decline in cork production.
Keywords: Bark; Porthetria dispar; Quercus suber